Metodología de diseño y optimización de filtros para 5g (2021)
In order to fulfill with 5G usage, higher transmission rates, rage capacity and less latency are required. Furthermore, wireless communications require most of the spectrum to be used. This paper presents the design and simulation of a pass-band filter in the 25 GHz band using a W-34 rectangular waveguide. In order to meet the requirements, a 4th order Chebyshev response with a lower band transmission zero is used. This is physically done with a box section topology. Moreover, characterization of a symmetric inductive iris and an asymmetric capacitive iris are presented, showing the susceptance according to the iris width. These previous results are used in the process of obtaining irises? width that realize the coupling of the filter resonators. The filter is simulated on Ansys HFSS and a global optimization of physical dimensions is carried out to adjust its response. The final result gets a filter with a fractional bandwidth of 4%, with insertion loss of 1.88 dB and return loss of 4.53 dB in the band pass with reject of 40.83 dB in the lower band and 36.43 dB in the upper band. The results show a significant agreement between the theoretical transfer function and the initial simulation, as well as a vast improvement by global optimization in a reasonable time.